Associations between Sarcopenia and trajectories of activities of daily living disability: a nationwide longitudinal study of middle-aged and older adults in China from 2011 to 2018 - Lei Lan; ShiMiao Shao; Xiaowei Zheng (BMC, 2024)
Abstract Background Sarcopenia is an age-related clinical syndrome, which is associated with numerous adverse outcomes among older adults. The relationship between sarcopenia and activities of daily living (ADL) disability has been studied in China, but these findings usually focused on a single time point. The patterns of ADL can change over time and vary among individuals. Therefore, it is necessary to explore the association between sarcopenia and trajectories of ADL disability. Methods According to Asian Working Group for Sarcopenia (AWGS) 2019 criteria, muscle mass, muscle strength, and physical performance measurements were measured to diagnose sarcopenia. A six-item ADL score was used to measure ADL disability, and trajectories of ADL disability were identified by the latent class trajectory modelling (LCTM). Multiple logistic regression models were performed to examine the association between sarcopenia and trajectories of ADL disability. Results Among 9113 middle-aged and older adults, three trajectories of ADL disability were determined according to changes in ADL score during follow-up, including a mild-high trajectory (n = 648, 7.11%), followed by the low-mild trajectory (n = 3120, 34.24%) and low-low trajectory (n = 5345, 58.65%). After adjustment for covariates, severe sarcopenia was significantly associated with higher risks of being in the mild-high trajectory group (OR = 3.31, 95%CI: 2.10-5.22) and the low-mild trajectory group (OR = 1.44, 95%CI: 1.05-1.98), compared with the low-low trajectory group. This association was still observed when stratified by age and gender. In addition, participants with sarcopenic obesity were associated with a higher risk of ADL disability (OR = 3.99; 95% CI: 2.50-6.09). Conclusions Among the middle-aged and older Chinese adults, sarcopenia and sarcopenic obesity were both associated with persistent higher trajectories of ADL disability. It suggested that early interventions to sarcopenia and sarcopenic obesity among the middle-aged and older adults may reduce the progression of ADL disability.